Optimal design of brace-viscous damper and pendulum tuned mass damper using Particle Swarm Optimization. (July 2021) - Pourzangbar, Ali; Vaezi, Mostafa
Highlights: Brace-viscous and pendulum tuned mass dampers are implemented to a jacket platform. Particle Swarm Optimization (PSO) is chosen to do the optimization process. Combined optimal BVDS-PTMD outperforms the BVDS and PTMD. Using optimal BVDS-PTMD the standard deviation of deck displacement decreased by 36.54%. Optimal BVDS outperforms Optimal PTMD regarding the deck displacement and base shear force. Abstract: We implemented Particle Swarm Optimization (PSO) to determine the most optimal properties of the brace-viscous damper system (BVDS), pendulum tuned mass damper (PTMD), and combined BVDS-PTMD system in mitigation of dynamic response of a jacket platform. To do this, a scaled prototype of an offshore jacket is numerically simulated in ANSYS subjected to ocean waves. Concerning BVDS, at each story, the variables being optimized are (1) BVDS configuration such as chevron, toggle, diagonal; (2) damping coefficient, and (3) brace area. The properties of PTMD being optimized are the damping ratio ( ξ d ), frequency ratio ( β ), structural excitation frequency ratio ( α ), and mass ratio ( m ¯ ). To do the optimization, the results of ANSYS are exploited to calculate the PSO cost function (standard deviation of deck displacements ( σ s d )). Regarding the deck displacement and base shear force, the optimization results proved that the optimal BVDS-PTMD combined system outperforms the optimal BVDS and the optimal BVDS performance is better than that of the PTMD system. Both in the optimal BVDS and integrated BVDS-PTMD, the chevron configuration for the top floor and toggle configuration for the first to third floors are evaluated as the optimum arrangement by the optimization algorithm.